Psychometric appraisal of the Kurdish version of the Revised Hearing Handicap Inventory-Screening - Zmnako, Sherko Saeed F. (Scientific reports, 2024)
The Revised Hearing Handicap Inventory-Screening (RHHI-S) is a robust 10-item Patient-Reported Outcome Measure (PROM) that can quantify impacts of hearing loss (HL). Employing a cross-sectional study, the psychometric properties of a cross-culturally adapted Kurdish version of RHHI-S (RHHI-S-CK) were investigated. According to the degrees of HL, 168 enrollees (64.3% male; mean-age 63.1 ± 12.6 years) were divided into three subgroups; that is, mild ( n = 56; 67.9% male; mean-age 60 ± 12.5 years), moderate ( n = 64; 60.9% male; mean-age 64.6 ± 12.5), & moderately-severe ( n = 48; 64.6% male; mean-age 63.1 ± 12.6). The internal cohesion among the items was confirmed by Cronbach’s alpha (0.94). Confirmatory factor analysis recognised structural validity when a strong unidimensional factor was extracted. Convergent validity was verified ( P-value < 0.001 ) via Spearman’s correlation between the scale and a subjective correlator (visual analogue scale). A large effect size (0.88) from Kruskal-Wallis & Dunn-Bonferroni post-hoc tests established the discrimination between different degrees of HL. Lastly, intraclass correlation coefficient (ICC) proved the external reliability of the adapted version of the tool (Test-retest ICC = 0.95). RHHI-S-CK is a robust PROM that can measure the impacts of HL in adults across all age ranges. Accordingly, RHHI-S-CK augmented the clinical and academic practice of the Kurdish medical community.